Developing team decision-making: a holistic framework integrating both on-field and off-field pedagogical coaching processes - Richards, P.; Collins, D.; Mascarenhas, D. R. D. (Sports Coaching Review, 2017)
This paper explores the complexity of developing decision-making (DM) skills in team sports. Research from the domains of motor control, perception and pedagogy (Teaching Games for Understanding and Game Sense) has significantly enhanced our knowledge of DM in sport. However, such studies although contributing knowledge, have explored elements of DM in isolation and many have failed to consider the naturalistic context in which decisions are made. Additionally research has often ignored the complexity of exploring DM within a team setting. Using the Naturalistic Decision Making paradigm, this paper proposes two interconnected models designed to develop individual/team DM. Model 1 presents a layering approach where performer`s cognitions, situational factors and the performance setting are explored. Model 2 places this framework in the context of on-field and off-field training/competitive environments. It is envisaged that this paper will open discussions as to how researchers and practitioners develop DM skills in team sports.